Variation of Red Blood Cell Distribution Width and Mean Platelet Volume after Moderate Endurance Exercise - Giuseppe Lippi; Gian Luca Salvagno; Elisa Danese; Cantor Tarperi; Gian Cesare Guidi; Federico Schena (Advances in Hematology)
Although physical exercise strongly influences several laboratory parameters, data about the hematological changes after medium distance running are scarce. We studied 31 middle-trained athletes (mean training regimen 217±32 min/week) who performed a 21.1 km, half-marathon run. Blood samples were collected before the run, at the end, and 3 and 20 hours thereafter. The complete blood count was performed on Advia 2120 and included red blood cell (RBC), reticulocyte, and platelet counts; hemoglobin; mean corpuscular volume (MCV); mean corpuscular hemoglobin (MCH); reticulocyte haemoglobin content (Ret CHR); RBC distribution width (RDW), mean platelet volume (MPV). No significant variations were observed for MCH and Ret CHR. The RBC, reticulocyte, and hemoglobin values modestly decreased after the run. The MCV significantly increased at the end of running but returned to baseline 3 hours thereafter. The RDW constantly increased, reaching a peak 20 hours after the run. The platelet count and MPV both increased after the run and returned to baseline 3 hours thereafter. These results may have implications for definition of reference ranges and antidoping testing, and may also contribute to explaining the relationship between endurance exercise and mortality, since previous studies reported that RDW and MPV may be significantly associated with cardiovascular disease.